Clinical Features and Potential Mechanisms Relating Neuropathological Biomarkers and Blood-Brain Barrier in Patients With Alzheimer’s Disease and Hearing Loss - Zhang, Wei-jiao; Li, Dan-ning; Lian, Teng-hong; Guo, Peng; Zhang, Ya-nan; Li, Jing-hui; Guan, Hui-ying; He, Ming-yue; Zhang, Wen-jing; Zhang, Wei-jia; Luo, Dong-mei; Wang, Xiao-min; et al. (Frontiers in Aging Neuroscience, 2022)
Background To explore clinical features and potential mechanisms relating to neuropathological biomarkers and blood-brain barrier (BBB) in Alzheimer’s disease (AD) and hearing loss (HL). Methods Total 65 AD patients were recruited and auditory function was assessed by threshold of pure tone audiometry (PTA) . Patients were divided into AD with HL(AD-HL) and AD with no HL (AD-nHL) groups based on standard of World Health Organization. Clinical symptoms were assessed by multiple rating scales. The levels of neuropathological biomarkers of β amyloid1-42 (Aβ1-42) and multiple phosphorylated tau (P-tau), and BBB factors of matrix metalloproteinases (MMPs), receptor of advanced glycation endproducts, glial fibrillary acidic protein and low density lipoprotein receptor related protein 1 were measured. Results 1. Compared with AD-nHL group, AD-HL group had significantly impaired overall cognitive function and cognitive domains of memory, language, attention, execution, and activities of daily living (ADL) reflected by the scores of rating scales (P<0.05). PTA threshold was significantly correlated with the impairments of overall cognitive function and cognitive domains of memory and language, and ADL in AD patients (P<0.05). 2. P-tau (S199) level was significantly increased in CSF from AD-HL group (P<0.05), which was significantly and positively correlated with PTA threshold in AD patients. 3. MMP-3 level was significantly elevated in CSF from AD-HL group (P<0.05), which was significantly and positively correlated with PTA threshold in AD patients (P<0.05). 4. In AD-HL group, P-tau (S199) level was significantly and positively correlated with the levels of MMP-2 and MMP-3(P<0.05). Conclusions AD-HL patients have severely compromised overall cognitive function , multiple cognitive domains and ADL. The potential mechanisms of AD-HL involve elevations of AD neuropathological biomarker of P-tau (S199) and BBB factor of MMP3, and close correlations between P-tau (S199) and MMP-2/ MMP-3 in CSF. Findings from this investigation highly suggest significance of early evaluation and intervention of HL for delaying AD progression, and indicate new directions of drug development by inhibiting neuropathological biomarkers of AD and protecting BBB.